KEBIJAKAN DEVIDEN PADA INDEKS SAHAM LQ45 DI BURSA EFEK INDONESIA - Endang Lestari; Ardiani Ika Sulistyawati (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2017)
This study to be analyze how the influence of Return On Equity , Debt to Equity Ratio , Asset Growth , Cash Ratio, Insider Ownership , and Total Asset Turn Over the companies listed in Indonesia Stock LQ45 in BEI 2010-2014.Sampling technique in this research is by using explanatory research using quantitative approach . Sample obtainedand used is 12 Integration with the observation period of 5 years . The data used in this research is secondary dataanalysis method used is multiple regression analysis.The results showed that the adjusted R -square value of 0.542 .Simultaneously F count 12.051 table 4.9 , it can be said that the variable Return On Equity significant influence withthe positive direction of the Dividend Payout Ratio . Variable Total Asset Turn Over a significant effect but with anegative direction of the Dividend Payout Ratio . While the variable Debt to Equity Ratio , Asset Growth , Cash Ratio, and Insider Ownership no significant effect on Dividend Payout Ratio.Keywords : Return On Equity, Debt to Equity Ratio, Asset Growth, Cash Ratio, Insider Ownership , Total AssetTurnover, Dividend Payout Rati .